About the vertical structure of currents in the intermediate Rio de la Plata: Observational study - Dragani, Walter Cesar (2002)
The Río de la Plata is one of the most important estuarine systems of the world and the most developed basin of eastern South America. Water levels and currents have been measured at many locations of the river and a number of depth-integrated (2-D) models have been applied to determine its circulation. Nevertheless, the three-dimensional characteristics of the currents have been never analyzed by means of 3-D models. The lack of direct measurements of current profiles is a possible reason that explains the absence of 3-D models implemented in the estuary. In this work current data measured using an Acoustic Doppler Current Profiler are presented to show the complex vertical structure of currents in the intermediate Río de la Plata. In February 2-3 2000, a transect of approximately 16 Km long was repeated eleven times during 25 hours obtaining one current profile (0.5-m vertical resolution) every 45 seconds. After applying a specific processing the EW and NS components of the velocity were obtained for each of the 85 by 12 time series placed regularly in a rectangular matrix throughout the transect. These time series were fitted to two sinusoids with M2 (12.42 hours) and O1 (25.82 hours) periods using least squares fitting techniques. This procedure yields the M2 and O1 amplitudes and phases of the EW and NS components of the current at each grid point in addition to the both components corresponding to the mean flow (residuals). In this paper amplitude and phase of the components associated to the M2 constituent and mean flow are described. Results showed that currents present strong vertical gradients not only in the semidiurnal constituent but also in the mean flux in the intermediate zone of the Río de la Plata. Although the intermediate Río de la Plata is a very shallow basin results revel that inversion of current from upper to bottom layers occurs. These results indicate that currents respond strongly to the local winds but their effects are mainly manifested at the upper layer. Finally, our results indicate that 3-D models should be used in order to obtain a reliable and complete representation of currents in the Río de la Plata.